Analisis Implementasi Anggaran Pembangunan Kelistrikan (Studi terhadap Perda APBD Sektor Pertambangan dan Energi Kabupaten Bulungan Tahun 2010-2012) - Romadhoni, Wibowo; Pribadi, Ulung (Universitas Muhammadiyah Yogyakarta, 2014)
This research is descriptive research. Result research show do not have perda that special regulate about develop-ment electricity. success develop supporter factor implementation budget electricity can be seen from aspects imple-mentation success scaling, namely: implementation policy support development budget in electricity developmentimplementation. Support sources policy in Perda APBD mining sector implementation and Energi Kabupaten Bulunganwith the existence ofÂ budget that is large and the increase human resource. Support communication inter relatedorganisation, between Dinas Pertambangan and PT. PLN as well as BAPPEDA intertwined coordination that is good.Executive body characteristic, and tendency all executive apper tain good with the existence ofÂ programâprogramactivity that execute favorably. Executive activity very support so that target desired can achieved. Inside economycondition thing, social, and politics can be said that that aspect very suppor t Implementasi success with all set him theneed for energy electricity certainly will improve social and economic growth as well as stability politics. Factors thatstill become obstacle to Perda APBD Sektor Pertambangan success implementation and Energi Bulungan regency isexecutive apparatus number, facility and infrastructure stillÂ very less, inside inability contractor perform activity, andnot smooth electricity in development because condition geography that is wide and out ofÂ reach.